Material Development Strategy of Lightweight Solid Oxide Fuel Cells for Airplane System Electrification. (10th July 2019) - Hashimoto, Shinichi; Hirota, Tomohisa; Suzuki, Kenji; Namioka, Tomoaki; Ito, Hibiki; Miyata, Ryuichi; Kobayashi, Keiko; Yashiro, Keiji; Takamura, Hitoshi; Kawada, Tatsuya; Yoshimi, Kyosuke; Kijima, Norito; et al.
Abstract : In this study, first, power densities by using SOFC system for APU of regional jets were estimated based on metal supported SOFC system and compared with those in gas turbine APU. As the second, based on the results of power density analysis in the SOFC system, all materials making up the cell stacks are examined and developed for the weight reduction. Such material development strategy is the first trial without precedent in SOFC development history.